Effect of Classroom Climate and Parental Awareness on Academic Achievement of Secondary School Students - Dwivedi, Ramesh Dhar (JOURNAL OF INDIAN EDUCATION, 2011)
The success of school life is judged by academic achievement of the student. Achievement depends on a number of factors like learner’s ability, personality, intelligence, socio-economic conditions as well as environment of school, classroom and home. The feelings and emotions being shaped in a particular climate of a particular classroom is the basic source of motivation to learn something. The physical structure of classroom as well as interaction between student and teacher constitute classroom climate which shape the educational attainment of the child and if students feel themselves tense and hostile they may be led to poor learning. Similarly the students whose parents show keen interest in their studies achieve better in exams than the students whose parents show less interest in their studies. Besides the classroom climate and parental awareness it was also observed that location of the school has an important influence on achievement and students of urban area have an edge over the students of rural area in their academic achievement.